Pencatatan Perkawinan dan Sanksi Hukumnya: Studi Kritis Terhadap Asas Kepastian, Keadilan, dan Kemanfaatan - Kurniawan, Ardian; Padli, Hamdani; Tauvani, A. Yuli; Rahayu, Karlina; Sumanto, Dedi (Al-Mizan (e-Journal), 2025)
The policy of sanctioning laws and regulations for violations of marriage registration provides space for discourse in both a philosophical and practical context. The understanding of marriages that are not recorded encompasses violations in juridical terminology, as the content of sanctions can have actual implications for the emergence of problematic law enforcement in the field of marriage. This research was conducted to analyze and find out what the juridical implications are for the sanction policies contained in various legal regulations related to violations of marriage registration. The literature study method is the method used in this research, by collecting data through a review of various kinds of legal rules. This study uses a statutory regulation approach in examining regulations related to legal issues regarding sanctions for violations of marriage registration. Several policies that contain sanctions for violations of the legal registration of marriages are considered inappropriate because they cannot be met on a fundamental basis. There is a bias in the authority of law enforcement in the object of this violation of marriage registration. Legal ambiguity can arise in the process of sentencing if it is associated with the content of sanctions that have a tendency not to be in the realm of private law.